Search for the production of (WWW -/+)-W-+/--W-+/- events at root s=13 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2019)
A search for the production of events containing three W bosons predicted by the standard model is reported. The search is based on a data sample of proton-proton collisions at a center-of-mass energy of 13 TeV recorded by the CMS experiment at the CERN LHC and corresponding to a total integrated luminosity of 35.9 fb(-1). The search is performed in final states with three leptons (electrons or muons), or with two same-charge leptons plus two jets. The observed (expected) significance of the signal for (WWW -/+)-W-+/--W-+/- production is 0.60 (1.78) standard deviations, and the ratio of the measured signal yield to that expected from the standard model is 0.34(-0.34)(+0.62) . Limits are placed on three anomalous quartic gauge couplings and on the production of massive axionlike particles.
Keywords: HADRON COLLIDERS; CP CONSERVATION